The relationship between renal P-glycoprotein expression and response to steroid therapy in childhood nephrotic syndrome - Türkmen, Mehmet; Torun-Bayram, Meral; Soylu, Alper; Özer, Erdener; Sarıoğlu, Sülen; Kavukçu, Salih (The Turkish Journal of Pediatrics, 2013)
In this study, we aimed to investigate the relationship between renal P-glycoprotein (rP-gp) expression and response to corticosteroid therapy in childhood nephrotic syndrome (NS). Expression of rP-gp was evaluated prior to non-steroid immunosuppressive therapy in children with NS (Group 1), prior to any treatment in children with immunoglobulin (Ig)A nephropathy (Group 2), and during renal donation in healthy adults (Group 3); mesangial proliferation was evaluated in Groups 1 and 2. Total dosage of steroid was calculated in Group 1. The ratio of rP-gp (+) glomeruli was higher in Group 1 than Group 3 (33.8 ± 27.1% vs 4.7 ± 4.6%, p=0.000). There were no rP-gp (+) glomeruli in Group 2. The rate of mesangial proliferation was similar in Groups 1 and 2. There was no statistically significant correlation between rP-gp expression and total steroid dosage (r=0.455, p=0.160). Our findings showed that rP-gp expression is increased in patients receiving steroid therapy for NS regardless of the cumulative steroid dosage and mesangial cell proliferation.